Recycling of polymers : methods, characterization and applications - Francis, Raju (Wiley-VCH, 2016)
This timely reference on the topic is the only book you need for a complete overview of recyclable polymers. Following an introduction to various polymer structures and their resulting properties, the main part of the book deals with different methods of recycling. It discusses in detail the recycling of such common polymers as polyethylene, polypropylene and PET, as well as rubbers, fibers, engineering polymers, polymer blends and composites. The whole is rounded off with a look at future technologies and the toxicological impact of recycled polymers. An indispensable reference source for those working in the field, whether in academia or industry, and whether newcomers or advanced readers.